Study of the properties of lubricating oils obtained from biodiesel - Cruz, Andreza de Faria Alves; de Carvalho, Raquel Moreira Maduro; de Oliveira, Fábio Celso (Eclética Química, 2020)
In this work, nine different biodiesels were obtained by transesterification reaction with three types of vegetable oils and three variant alcohols. The objective was to analyze them physicochemically before and after they went to the engine, to know if they had the necessary properties to act as lubricants. Subsequently, the same biodiesels were analyzed in the engine in order to observe the behavior of their dynamic viscosities, to evaluate if they were similar or superior to commercial lubricants. It was possible to note that all biodiesel produced are within the National Agency for Petroleum, Natural Gas and Biofuels (ANP) legislation and presented as potential lubricants, due to the kinematic viscosity behavior when compared before and after the engine. These results made them possible replacements for commercial lubricants, besides having greater advantages for the engine and the environment. However, although coconut oil-derived biodiesel has good yields, it is not promising because, at temperatures below 25 °C tends to solidify, causing short, medium- and long-term engine parts wear.